The Effectiveness of a Proposed Teaching Program for Brain-Based Learning on An Attitude Toward Learning Among University Students (Raparin Journal of Humanities (RJH), 2025)
The aim of this research is to build a proposed curriculum of brain-based learning in the attitude toward learning for students at Koya University، then to determine the effectiveness of the knowledge-based learning strategy on the direction of learning for students by showing the statistical evidence difference between the pre-test and the backward test، to find out the effectiveness of the program for orientation for learning. Receiving from previous and surveyed literatures and researches, which consisted of 52 sections, was divided into four dimensions (scientific, emotional, behavior, behavior intention) After extracting the psychometric characteristics (truthfulness and stability), the scale was present. Then the researchers developed a teaching program to develop the orientation for learning by university students, and applied the program to the sample of the study, which consisted of 38 students and were divided. After many training and training, they were selected into two groups. The experimental group consisted of: (19) students who were taught by the proposed student-based learning program, the organizing group, consisting of 19 students who were taught in the normal way, used the Statistical Program Paired Samples T-test for two paired samples, to draw the results of the study, which was as follows:  It was found that there was no statistical evidence difference between the pre-test and the later test, and finally, according to the obtained results, the recommendations and recommendations.